Dynamics and Diffusion in Photosynthetic Membranes from Rhodospirillum Photometricum - Scheuring, Simon (Biophysical Society, 2006)
Photosynthetic organisms drive their metabolism by converting light energy into an electrochemical gradient with high efficiency. This conversion depends on the diffusion of quinones within the membrane. In purple photosynthetic bacteria, quinones reduced by the reaction center (RC) diffuse to the cytochrome bc(1) complex and then return once reoxidized to the RC. In Rhodospirillum photometricum the RC-containing core complexes are found in a disordered molecular environment, with fixed light-harvesting complex/core complex ratio but without a fixed architecture, whereas additional light-harvesting complexes synthesized under low-light conditions pack into large paracrystalline antenna domains. Here, we have analyzed, using time-lapse atomic force microscopy, the dynamics of the protein complexes in the different membrane domains and find that the disordered regions are dynamic whereas ordered antennae domains are static. Based on our observations we propose, and analyze using Monte Carlo simulations, a model for quinone diffusion in photosynthetic membranes. We show that the formation of large static antennae domains may represent a strategy for increasing electron transfer rates between distant complexes within the membrane and thus be important for photosynthetic efficiency.